2022
DOI: 10.3390/bioengineering9060243
|View full text |Cite
|
Sign up to set email alerts
|

The Footprint of Exosomes in the Radiation-Induced Bystander Effects

Abstract: Radiation therapy is widely used as the primary treatment option for several cancer types. However, radiation therapy is a nonspecific method and associated with significant challenges such as radioresistance and non-targeted effects. The radiation-induced non-targeted effects on nonirradiated cells nearby are known as bystander effects, while effects far from the ionising radiation-exposed cells are known as abscopal effects. These effects are presented as a consequence of intercellular communications. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 149 publications
0
12
0
Order By: Relevance
“…RIBE-induced exosomes can play positive and negative roles in the cells—ncRNAs and ncRFs in exosomes and EVs can regulate gene expression at the destination cells by either activating defense mechanisms or causing instability, increasing inflammation and preparing cells for malignization events [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…RIBE-induced exosomes can play positive and negative roles in the cells—ncRNAs and ncRFs in exosomes and EVs can regulate gene expression at the destination cells by either activating defense mechanisms or causing instability, increasing inflammation and preparing cells for malignization events [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor cells are killed by the rays and the cellular contents are released. The contents can activate the immune system in vivo, which can kill metastatic tumor cells [ 20 ]. The researchers who conducted the ACCORD trial reported that the mOS of metastatic PDAC patients treated with FOLFIRINOX was 11 months, which was longer than the mOS of 6 months found in the present study [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…After PSM, the effect of radiotherapy was still obvious. Radiotherapy is expected not only to eliminate local lesions but also to activate the immune system to kill metastatic tumor cells through radiation-induced bystander effects [21]. SBRT has been reported to induce immune-related cell death in pancreatic cancer in both preclinical models and tissue samples from patients [22,23].…”
Section: Prognostic Nomogram Building and Validationmentioning
confidence: 99%